Arthroscopic Repair of Massive Rotator Cuff Tears: Outcome and Analysis of Factors Associated With Healing Failure or Poor Postoperative Function. (July 2013) - Chung, Seok Won; Kim, Joon Yub; Kim, Min Hyung; Kim, Sae Hoon; Oh, Joo Han
Background: Many patients with an unhealed cuff after repair show functional improvement. Purpose: To evaluate outcomes of arthroscopically repaired massive rotator cuff tears and to identify prognostic factors affecting rotator cuff healing and functional outcome, especially in patients with failed rotator cuff healing. Study Design: Case series; Level of evidence, 4. Methods: Among 173 patients who underwent arthroscopic repair of a massive rotator cuff tear, 108 patients with a mean age of 63.7 years were included. Outcome evaluation was completed both anatomically (CT arthrography or ultrasonography) and functionally at a minimum of 1 year postoperatively; mean follow-up period was 31.68 ± 15.81 months. Various factors affecting cuff healing were analyzed, and factors affecting functional outcome were evaluated in patients with failed repairs using both univariate and multivariate analyses. Results: The anatomic failure rate was 39.8% in arthroscopically repaired massive rotator cuff tears; however, functional status significantly improved regardless of cuff healing ( P < .05). Several factors were associated with failure of cuff healing in the univariate analysis, but only fatty infiltration (FI) of the infraspinatus was significantly related to healing failure in the multivariate analysis ( P = .04). Among patients with failed rotator cuff healing, only reduced postoperative acromiohumeral distance (AHD) was related to poor functional outcome in the multivariate analysis ( P = .01), with a cutoff value of 4.1 mm. Conclusion: Despite a high rate of healing failures, arthroscopic repair can be recommended in patients with massive rotator cuff tears because of the functional gain at midterm follow-up. Higher FI of the infraspinatus was the single most important factor negatively affecting cuff healing. In cases of failed massive rotator cuff repair, no preoperative factor was able to predict poor functional outcome; reduced postoperative AHD was the only relevant functional determinant in the patients' eventual functional outcome and should be considered when ascertaining a prognosis and planning further treatment strategies.